Espaço e lugar privilegiado para formação de professores Instituto de Educação "Fernando Costa" (1953-1975) - Conceição, Aline de Novaes (Editora Oficina Universitária, 2020)
The Institutes of Education were complex institutions, whose central axis was teacher training articulated with various levels of education that operated in the institutes themselves. In this book, Aline de Novaes Conceição reconstitutes elements of a history of the "Fernando Costa" Institute of Education, which operated from 1953 to 1975, focusing on its installation, closure and the experiences of the institution's subjects, that is, students, family members, teachers, directors and supervisors. The author explains that the researched institution was positively received by the inhabitants of the city and the closure caused indignation and contrary demonstrations. The "Fernando Costa" Institute of Education worked by seeking a dialogue with the locality, with teacher training being carried out in conjunction with the practice experienced by the subjects in the Annex Primary Course, in Secondary Education and in the Collegiate Course, this institute being a privileged space for the training of teachers, whose courses located in this space, had conflicts involving directors, teachers and students.